2020
DOI: 10.5194/hess-24-5875-2020
|View full text |Cite
|
Sign up to set email alerts
|

New measures of deep soil water recharge during the vegetation restoration process in semi-arid regions of northern China

Abstract: Abstract. Desertification in semi-arid regions is currently a global environmental and societal problem. This research attempts to understand whether a 40-year-old rain-fed Artemisia sphaerocephala Krasch sand-fixing land as part of the Three North Shelterbelt Program (3NSP) of China can be developed sustainably or not using a newly designed lysimeter to monitor the precipitation-induced deep soil recharge (DSR) at 220 cm of depth. Evapotranspiration is calculated through a water balance equation when precipit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Increased temperature and reduced precipitation can lead to meteorological drought, causing water shortages in the atmosphere and soil, exacerbating vegetation drought stress, and inhibiting vegetation growth [40]. Previous studies have shown that climate warming is the main factor influencing vegetation NDVI changes in many areas of the middle and high latitudes of the Northern Hemisphere [41][42][43][44][45]. Bao et al studied the NDVI and found a positive correlation with precipitation but a weak correlation with temperature, implying that precipitation amounts in the growing season are a key factor regulating vegetation dynamics at the plateau scale.…”
Section: Discussionmentioning
confidence: 99%
“…Increased temperature and reduced precipitation can lead to meteorological drought, causing water shortages in the atmosphere and soil, exacerbating vegetation drought stress, and inhibiting vegetation growth [40]. Previous studies have shown that climate warming is the main factor influencing vegetation NDVI changes in many areas of the middle and high latitudes of the Northern Hemisphere [41][42][43][44][45]. Bao et al studied the NDVI and found a positive correlation with precipitation but a weak correlation with temperature, implying that precipitation amounts in the growing season are a key factor regulating vegetation dynamics at the plateau scale.…”
Section: Discussionmentioning
confidence: 99%
“…To calculate the proportion of atmospheric water (precipitation) absorbed by Tamarisk to the total water consumption in a growing season, we carried out a Tamarisk water balance observation experiment through in situ observations of precipitation, soil moisture, and DSR. To monitor DSR, a new lysimeter was used in this research [ 41 ]. This new lysimeter was assembled with two parts: a balanced part and a measurement part.…”
Section: Methodsmentioning
confidence: 99%
“…Natural herbaceous vegetation mainly includes Artemisia ordosica , Nitraria tangutorum , and so on. The experimental site is located in an artificial Tamarisk Ramosissima forest with relatively flat terrain and small undulation [ 31 ]. The Tamarisk forest is about 30 years old and is planted with a row space of 3 m × 2 m. The average base diameter of Tamarisk is 9.34 cm, the average height of Tamarisk is 2.95 m, and the average crown width of Tamarisk is 2.69 m × 2.32 m. After excavation, we find that the deepest root depth of native plants is about 6 m, but most of the roots of artificial vegetation are concentrated at 0–1.5 m depths.…”
Section: Research Areamentioning
confidence: 99%